Transcriptomics‐based analysis of the causes of sugar receding in Feizixiao litchi (Litchi chinensis Sonn.) pulp - Peng, Junjie; Du, Jingjia; Wuqiang, Ma; Chen, Tiantian; Shui, Xian; Liao, Haizhi; Lin, Xiaokai; Zhou, Kaibing (Frontiers in Plant Science, 2022)
To investigate the causes of the “sugar receding” in ‘Feizixiao’ litchi (Litchi chinensis Sonn.) pulp, the main sugar contents and sucrose metabolism enzyme activities were measured in pulp obtained in 2020 and 2021. Pulp RNA obtained in 2020 was extracted at 35, 63, and 69 days after anthesis (DAA) for transcriptome sequencing analysis. The differential expression of genes was verified by real-time PCR for both years. The results showed that after 63 DAA, the contents of soluble sugars and sucrose decreased, and the contents of fructose and glucose increased in both years. The dynamic changes in sucrose metabolism enzyme activities were similar in both years. After 63 DAA, except for acid invertase (AI) in 2021, the activities of other enzymes decreased significantly, and the net activity of sucrose metabolism enzymes showed a strong sucrose cleavage activity. There were 18061, 19575, and 985 differentially expressed genes in 35 d vs. 63 d, 35 d vs. 69 d, and 63 d vs. 69 d, respectively. Ninety-one sugar metabolism genes were screened out, including sucrose synthase (SS), sucrose phosphate synthase (SPS), AI, neutral invertase (NI), hexokinase (HK), glucose 6-phosphate dehydrogenase (G6PD), 6-phosphogluconate dehydrogenase (6PGD), phosphofructokinase (PFK), and pyruvate kinase (PK) genes. In 63 d vs. 69 d, seventy-five percent of sucrose metabolism genes were downregulated, seventy-seven percent of genes in glycolysis (EMP) were upregulated and the PFK genes were significantly upregulated. There was a significant linear correlation between the expression of 15 genes detected by real-time PCR and the transcriptome sequencing results (r2020 = 0.9139, r2021 = 0.8912). These results suggest that the upregulated expression of PFK genes at maturity may enhance PFK activity and promote the degradation of soluble sugar in pulp through the EMP pathway, resulting in decreased soluble sugar and sucrose contents and “sugar receding” in pulp. Moreover, the downregulated expression of sucrose metabolism genes in pulp decreased the activities of these enzymes, but the net activity of these enzymes resulted in cleaved sucrose and replenished levels of reducing sugars, resulting in a stable reducing sugar content.